Coal use for world economy: Provision and transfer network by multi-region input-output analysis. (1st February 2017) - Xia, X.H.; Chen, B.; Wu, X.D.; Hu, Y.; Liu, D.H.; Hu, C.Y.
Abstract: Concerns surrounding climate change and environmental challenge make the coal utilization network essential not only for understanding the pattern of energy provision and transfer, but also for illustrating the interaction between anthropogenic activities and ecological systems at global level. This paper fills the research gap by dint of multi-regional input output model to outline coal embodied routes from natural boundaries to economic activities, and to identify the central hubs in the global coal supply chain, based on the most recent available statistics for 2011. As the economic value and environmental influences of different kinds of coals could be remarkably diverse, the separation of coal categories in systematic analysis could provide fundamental information regarding the displacement and teleconnection of coal utilization in the world. The estimation shows that in weight 64.99% of coal direct supply is ultimately embodied in international trade, indicating the crucial roles of trade interlinks in global coal utilization. Apart from this, the findings pertinent to sectoral structure, regional supply chain and per capita characteristics of coal embodied utilization, could be valuable to identify the global energy routes driven by international trade as well as to facilitate energy and environmental policy. Highlights: High concentration of embodied coal utilization in specific sectors and regions are detected. The embodied coal in international trade adds up to 16.57 billion tons, accounting for 64.99% of global total coal exploitation. Bilateral embodied flows of coal sub-categories between main economies are visualized. The ratio of coal utilization embodied in international trade to direct supply is figured out. The highest per capita rates of coal embodiment are Iceland for anthracite, Hong Kong for coking coal and other bituminous coal, USA for sub-bituminous coal, Serbia for lignite and Finland for peat.